login
A176982
Sequence defined by the recursion a(n) = (1/2)*((1-signum(abs(b(n))-n))*b(n)+(1+signum(abs(b(n))-n))*a(n-1)), with a(1)=1 and b(n)=1+a(n-1-(n mod a(n-1)))-(-1)^n*a(n-1).
1
1, 1, 2, 1, 3, 1, 3, 1, 3, -1, -1, 1, 3, -3, -5, 3, 1, 1, 3, -1, -1, 1, 3, 1, 3, 1, 3, -1, -1, 1, 3, -3, -5, 5, 11, -13, -9, 21, 21, -21, -21, 1, 3, -23, -21, 1, 3, 1, 3, 1, 3, -1, -1, 1, 3, -3, -5, 7, 11, -9, -9, 9, 19, -21, -11, 1, 3, -13, -33, 23, 11, -21, -11, 1, 3, -1, -1, 1, 3, -3
OFFSET
1,3
COMMENTS
Behaves erratically (see linked picture).
There is a similar sequence with a(1)=2.
REFERENCES
G. Balzarotti and P. P. Lava, 103 curiosità matematiche, Hoepli, 2010, p. 276.
LINKS
John A. Pelesko, Generalizing the Conway-Hofstadter $10,000 Sequence, Journal of Integer Sequences, Vol. 7 (2004), Article 04.3.5.
Klaus Pinn, A Chaotic Cousin Of Conway's Recursive Sequence, arXiv:cond-mat/9808031, 1998.
FORMULA
a(n) = (1/2)*((1-signum(abs(b(n))-n))*b(n)+(1+signum(abs(b(n))-n))*a(n-1)), with a(1)=1 and b(n)=1+a(n-1-(n mod a(n-1)))-(-1)^n*a(n-1).
EXAMPLE
a(1)=1.
b(2)=signum(abs(1+(2-1-(2 mod 1))-(-1)^2*1)-2)=signum(abs(1+1-1)-2)=-1.
a(2)=(1/2)*(1+1)*1+(1/2)*(1-1)*1=1+0=1.
MAPLE
P:=proc(i) local a, n; a:=array(1..50000); a[1]:=1; print(a[1]); for n from 2 by 1 to i do a[n]:=1/2*(1-signum(abs(1+a[n-1-(n mod (a[n-1]))]-(-1)^n*a[n-1])-n))*(1+a[n-1-(n mod (a[n-1]))]-(-1)^n*a[n-1])+1/2*(1+signum(abs(1+a[n-1-(n mod (a[n-1]))]-(-1)^n*a[n-1])-n))*a[n-1]; print(a[n]); od; end: P(10000);
CROSSREFS
KEYWORD
sign,look
AUTHOR
EXTENSIONS
Entries and formula corrected by Paolo P. Lava, May 04 2010
a(3) corrected by N. J. A. Sloane, Oct 02 2010
STATUS
approved